From micro to macro adventures of a wandering physicist - Vedral, Vlatko (Singapore World Scientific, 2018)
"This is a popular science book exploring the limits of scientific explanation. In particular, it debates if all sciences will ultimately be reducible to physics. The journey starts with physics itself, where there is a gap between the micro (quantum) and the macro (classical) and moves into chemistry, biology and the social sciences. Written by a practising scientist, this volume offers a personal perspective on various topics and incorporates the latest research"--
Includes bibliographical references and index.
Keywords: Physics -- Miscellanea; Science -- Miscellanea